Petrophysical properties of a siltstone reservoir - An example from the Montney Formation, western Canada. (February 2022) - Vaisblat, Noga; Harris, Nicholas B.; Ayranci, Korhan; Chalaturnyk, Rick; Power, Matthew; Twemlow, Cory; Minion, Nik
Abstract: The detrital grain size of siltstone reservoirs occupies a middle ground between sandstones and shales, both of which are better understood in terms of their petrophysical properties. Because siltstones can be important hydrocarbon reservoirs, we examine controls on petrophysical properties in the Lower Triassic Montney Formation in western Canada, which hosts world-class reserves of gas, gas liquids and oil. We focus on the effects of rock fabric (including grain size) and composition on pore system characteristics and permeability, drawing contrasts between the three reservoir types. The Montney Formation is an unconventional reservoir through most of its subcrop, with porosities ranging from ∼3 to 7.5% and permeabilities in the micro to nano Darcy range (6.5*10 −6 mD to 5.6*10 −2 mD). Shale reservoirs worldwide are characterized by similar porosity and permeability values, with porosity of up to 8% (rarely up to 15%) and permeability in the nano to micro-Darcy range. Quartz, clay, and organic matter abundance influence the petrophysical properties of the Montney siltstone. Quartz content exerts a positive control on both porosity and permeability by strengthening the rock framework and reducing porosity loss due to compaction. Elevated clay content is also associated with higher porosity and permeability, in part because of a depositional association with quartz, and in part because clays locally shelter interconnected primary porosity that promotes permeability. Organic matter content is negatively correlated to porosity and permeability despite the presence of organic matter porosity because relict oil (now solid bitumen) occludes primary pores and because other pore types contribute a greater fraction of the total pore volume. Lithofacies, characterized in four cores, are indistinguishable on the basis of petrophysical properties, due to their similar grain size and composition and the massive overprinting by shallow burial diagenesis. While the pore system evolution of sandstones is mainly controlled by the mechanical compaction of hard grains and cementation, pore system evolution of shales is primarily controlled by compaction of ductile grains and diagenesis of primary organic matter, in addition to cementation. Porosity and permeability values of the Montney siltstones are similar to those of shale formations, but the controls on pore system evolution of this intermediate grain size reservoir are predominantly controlled by processes similar to sandstones: compaction, cementation, and cement dissolution. Minor contribution from secondary porosity in bitumen affects some sections of the reservoir in a way that is similar, but not identical, to shale reservoirs. Graphical abstract: Finally, we showed that porosity and permeability values, as well aspore dimensions in the Montney siltstone are similar to those reported for shale reservoirs, despite the coarser grain size of the siltstone. Controls on the petrophysical properties differ between shale formation and this siltstone formation, related to fundamental differences in compaction, chemical diagenesis and the nature of organic matter maturation and migration. Highlights: Petrophysical properties of the Montney siltstone are similar to those of shales. The control over petrophysical properties of the siltstone and shales are different. Organic matter reduces porosity by narrowing pore throats. Porosity in organic matter is minor relative to other pore types in the siltstone. Controls over Petrophysical properties are quartz, clay, mica and organic matter.